EVALUATION OF LOOSELY BOUND WATER LOSS FROM DIFFERENT COMPOSITIONS OF GLASS IONOMER CEMENT - Asif, Muhammad; Ahmed, Muhammad Adeel; Malik, Sofia; Choudhry, Ziaullah; Mughal, Nouman; Naz, Farah (Journal of Ayub Medical College Abbottabad, 2019)
Background: Water is an essential component of glass ionomer cement. Water balance is probably the most important and least understood mechanism with the glass ionomer cement. Excessive water in glass ionomer produce weak cement while less amount of water produce cement which is relatively stronger initially but later results in the weakening of the cement. Water present in glass ionomer cement is classified according to its nature of being held in to the cement as tightly bound and loosely bound. The amount of loosely bound water loss from various composition of glass ionomer cement remains unknown. Methods: The study was conducted at the Department of Materials, Queen Mary University of London. Two different composition of glass ionomer cements were used in this experiment in which the amount of water absorbed by the different compositions of cement on 1, 3, 7 and 14 days were evaluated and the loss of water was measured after that period until the loss became constant. A total of 25 samples of each GIC composition, 5 samples were immersed in water for 24 hours, 5 in water for 3 days, 5 for 7 days and 5 for 14 days. The remaining 5 samples were directly placed into the desiccator without immersing it in the water. The total water content of both glass ionomer cements was calculated from its chemical composition. The samples were weighed every hour for first 3 hours and then every 24 hours until the weight of the sample became constant. Samples placed in water for 1, 3, 7 and 14 days were dried before weighing with a tissue. Results: The amount of water uptake in all the compositions was not that significant in relation to time. In case of Fuji IX, amount of water loss percentage did not vary with increasing time interval. The water loss was rapid in the first 24 hours but it slowed down with time and became constant after 3 days however in Ketac molar water loss slightly varied with time interval. Conclusion: It is concluded that the amount of water uptake in both glass ionomer cement is not significant in relation to time. The loss of loosely bound water becomes constant with time after 24 hours for both compositions of glass ionomer cements. Keywords: Loosly bound water; Glass ionomer; Cement